Freestanding few-layer sheets of a dual topological insulator - Anh, Mai Le; Potapov, Pavel; Lubk, Axel; Doert, Thomas; Ruck, Michael (npj 2D Materials and Applications, 2021)
The emergence of topological insulators (TIs) raised high expectations for their application in quantum computers and spintronics. Being bulk semiconductors, their nontrivial topology at the electronic bandgap enables dissipation-free charge and spin transport in protected metallic surface states. For application, crystalline thin films are requested in sufficient quantity. A suitable approach is the liquid phase exfoliation (LPE) of TI crystals that have layered structures. Bi2TeI is a weak 3D TI, which leads to protected edge states at the side facets of a crystal, as well as a topological crystalline insulator, which is responsible for protected states at the top and bottom faces. We developed an effective, scalable protocol for LPE of freestanding nanoflakes from Bi2TeI crystals. By heat treatment and sonication in isopropyl alcohol and poly(vinylpyrrolidone), crystalline Bi2TeI sheets with a thickness of 50 nm were obtained and can therefore be considered for further processing toward microelectronic applications.
CRIS-Team Scopus Importer:2022-04-14